MOLECULAR DETECTION OF ANCYLOSTOMA CANINUM: A PREDOMINANT ZOONOTIC HOOKWORM THAT AILS DOGS IN CHENNAI, TAMIL NADU, INDIA - Dhivya Bhoopathy; N. Jeyathilakan; A. Sangaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Hookworms of dogs especially Ancylostoma caninum and A.ceylanicum are the predominant gastro intestinal parasites of zoonotic significance. These are soil transmitted helminths (STH) whose larvae dwell in the soil and are capable of penetrating the host skin and then establishing itself in the intestine causing gastro-enteritis  and  anaemia.  Both  A.caninum  and  A.ceylanicum  can  infect dogs and their zoonotic potential is different and speciation becomes a necessity especially since it is difficult to distinguish the species morphologically. The current study was envisaged for molecular speciation of the hookworms affecting dogs in Chennai. A total of 185 faecal samples were examined of which 58 (31.35%) were positive samples and these were subjected to molecular speciation. The primers targeting ITS-1 gene of the parasite were designed and it was found that A.caninum  was  the  predominant  species  prevalent  amongst  dogs  in  Chennai.